Pengaruh Transaksi pada E-commerce dan Financial Literacy Terhadap Rasionalitas Perilaku Konsumsi Mahasiswa Fakultas Ekonomi Universitas Negeri Padang - Dela Wulandari; Menik Kurnia Siwi (Universitas Negeri Padang, 2022)
The purpose of this research is to analyze whether E-commerce transaction and Financial Literacy simultaneously affect the Rationality of Consumption Behavior of college Students of the Faculty of Economics, Padang State University. The independent variables are E-commerce transaction (X1) and Financial Literacy (X2), while the dependent variable is the Rationality of Consumption Behavior of Students Faculty of Economics, Padang State University. The type of research is quantitative research. The data collected in the form of numbers is the score from the collection of questionnaires on the rationality of consumption behavior, e-commerce transaction and financial literacy. The population is 2.385 student in 2017 until 2020 Economic Faculty undergraduate students. The samples is 97 respondent. The sampling technique used was proportionate stratified random sampling. Testing the instrument using validity and reliability tests. The data analysis method used multiple linear regression. The conclusion that is e-commerce transaction and financial literacy simultaneously have a significant effect on the rationality of consumption behavior of students of the Faculty of Economics, State University of Padang